Influência da linhagem e da idade de matrizes leves e semi pesadas na qualidade do ovo e do pinto de um dia - Ramos, Soliene Partata (2008)
This study aimed to evaluate the effect of age and lineage of layers breeders light and semi heavy on the quality of the egg, the pinto newly eclodido and performance of incubation. 3,456 eggs were used for breeding light (Dekalb White) and semi heavy (Bovans Goldline) in three different ages (young, old and middle age). The experiment was divided into two stages, at first we evaluate the characteristics of the eggs of a sample of 360 eggs (60 per treatment). In the second stage evaluated the performance of chicks hatching and quality of a sample of 3,096 eggs (516 per treatment). It was observed that the quality of the shell fell and the weight of the egg increased with the increase of age of the birds. The layers breeders Dekalb White eggs produced heavier in the middle ages and with better quality of bark at all ages. With the increasing age of the bird has increased the percentage of yolk and albumen decreases. This decrease was more pronounced in a manner eggs line Dekalb White. Eggs of the same lineage, layers breeders young and old had a higher percentage of egg yolk. The pH of the yolk and albumen increased with the ageing of layers breeding, which in old age, the egg line Dekalb White shows higher values for these variables that line Bovans Goldline. As for the assessment of incubation found that birds' eggs old line Bovans Goldline had greater percentage of weight loss during the incubation than those from Dekalb White layers breeders of the same age. The weight of pinto increased with increasing age of the leyer breeding and Dekalb White chicks born heavier that the Bovans Goldline. However, the relationship of chicks weight / weight of the egg was higher for chicks Bovans Goldline poultry young and middle age. The progeny Dekalb White was not influenced by the age of reproductive on this parameter. The percentage of females born in respect of fertile eggs was greater in the lineage Dekalb White. Since young matrices obtained lower values for this variable, regardless of their lineage. The female chicks Dekalb White, and had weights more uniform, had a higher percentage of bag viteline than the Bovans Goldline. The age of the matrix no effect on these variables. The percentage of the heart and lungs in the weight of the female chicks were not influenced by age or the lineage of breeding.